Effect of natural enemies on the invasion of the exotic plant buffalobur (Solanum rostratum Dunal.) in the arid oasis of Urumqi - Jian-Xiao, He; Yimingniyazi, Amanula (Frontiers in Environmental Science, 2023)
Studying the interspecific relationships of exotic species can provide an important theoretical basis for revealing the invasion processes of exotic species, predicting the scope and harm of proliferation, and subsequently suggesting reasonable prevention and control measures. Buffalobur (Solanum rostratum Dunal.) is a typical alien invasive plant that causes great harm in the oasis of the arid region of Xinjiang, being primarily distributed on both sides of the Toutun River and irrigated farmland. In the field, parasitic dodders (Cuscuta australis R. Br.) were observed, in addition to phytophagous insects such as potato beetles (Leptinotarsa decemlineata (Say)) and cotton bollworms (Helicoverpa armigera Hubner) that fed on the plant of the buffalobur. In order to explore the impact of dodder parasitism and insect feeding on buffalobur invasion, here, buffalobur was selected as the main research material, with the effects of different degrees of parasitism (non-parasitism, mild parasitism, severe parasitism), at different stages of parasitism (non-parasitism, seedling parasitism, flowering parasitism, fruit parasitism), and simulated insect feeding at different levels (nonparasitism, mild feeding, moderate feeding, and severe feeding) on the growth, development, and competitiveness of buffalobur being studied herein. The results showed that parasitism from dodders and feeding by phytophagous insects significantly reduced the biomass of buffalobur (P < 0.05), thus inhibiting its growth and development. In addition, the root-shoot ratio of the buffalobur was increased, which influenced its growth-defense strategy. At different degrees of parasitism from dodders and different degrees of feeding by phytophagous insects, the biomass of the buffalobur was decreased. However, the parasitism from dodders at different stages reduced the biomass and competitive ability of buffalobur (P < 0.05). Considering that the dodders and phytophagous insects